Modular instruction on modern algebra for first year fast learners - Abordo, Pilar Estamo; Baldo, Trinidad C. (1975)
This paper attempted to provide a much needed instructional material in the teaching of Modern Algebra to First Year fast learners. Included in this paper is a discussion of modular instruction which served as theoretical background for the proposed modules. The ten lessons selected for modularization were based on the ten basic units in modern algebra prescribed in the Teaching Guide for second year students issued by the Department of Education and Culture.
"October, 1975."
Thesis (Master of Arts in Teaching - Special education : Giftedness)--University of the Philippines, Diliman.
Keywords: Algebra -- Study and teaching (Secondary) -- Philippines; Teaching -- Philippines -- Aids and devices